Analysis of the Current State of Digitalization İmplementation in the Banking System of Azerbaijan - K. N. Atayev (Статистика и экономика, 2025)
Purpose of the study. The aim of this research is to investigate the current state of digitalization processes in the banking sector of the Republic of Azerbaijan, to identify the stages of development in this area, and to provide an objective evaluation of the achieved outcomes, potential opportunities, and emerging challenges associated with the implementation of digital banking. The study further involves an analysis of the effectiveness of digitalization policies in the national banking system on the basis of statistical data, regulatory legal acts, and state strategic documents.Materials and methods. The article provides a chronological analysis of the stages of digitalization in Azerbaijan’s banking sector, beginning from the early 1990s. Based on statistical data from the Central Bank of the Republic of Azerbaijan and the Association of Banks of Azerbaijan, the study examines year-by-year changes in the level of digitalization, supported by specific indexes. A comparative assessment of the current state of digital transformation within the context of the South Caucasus region is also presented. Furthermore, the article thoroughly explores existing cybersecurity strategies, types of threats, and their potential impact on the financial system, serving as a significant indicator of the application of a risk-based approach.Results. The process of digitalization in the banking sector of the Republic of Azerbaijan has evolved progressively since the 1990s and has ultimately led to the establishment of high-level digital banking services. Recent indexes confirm that the integration of mobile technologies, biometric identification systems, artificial intelligence algorithms, and fintech innovations has served as a significant catalyst for the transformation of this sector. According to statistical data for 2024, the majority of banking operations were conducted through electronic channels, while the volume of non-cash payments and electronic commerce transactions reached record levels. Strategic documents adopted by the state and regulatory initiatives undertaken by the Central Bank of Azerbaijan have been the principal driving forces behind this progress. Concurrently, the expansion of the digital environment has brought cybersecurity risks to the forefront, prompting the adoption of a new national cybersecurity concept for the period 2023–2026. Overall, digitalization has contributed to enhancing the quality, accessibility, and efficiency of banking services in the country, and has facilitated the sector’s transition toward a more innovative and customer-centric operational model. In the future, the key development directions of the banking sector wll be the improvement of digital credit products, the broad implementation of open banking technologies, the development of artificial intelligence-based services, and the issuance of a digital manat. Simultaneously, ensuring cybersecurity and improving the population’s level of digital literacy must remain among the primary priorities for the sustainable and secure implementation of this transformation.Conclusion. The results of the conducted research reveal that the process of digitalization in Azerbaijan’s banking sector has been developing in a consistent and systematic manner in recent years. Government-level programs, along with regulatory legal frameworks and strategic initiatives implemented by the Central Bank of Azerbaijan, have played a significant supportive role in advancing this direction.